The spectrum of progressive multifocal leukoencephalopathy: a practical approach - Bartsch, T.; Rempe, T.; Leypoldt, F.; Riedel, C.; Jansen, O.; Berg, D.; Deuschl, G. (European journal of neurology, 2019)
John Cunningham virus (JCV) infection of the central nervous system causes progressive multifocal leukoencephalopathy (PML) in patients with systemic immunosuppression. With the increased application of modern immunotherapy and biologics in various immune‐mediated disorders, the PML risk spectrum has changed. Thus, new tools and strategies for risk assessment and stratification in drug‐associated PML such as the JCV antibody indices have been introduced. Imaging studies have highlighted atypical presentations of cerebral JCV disease such as granule cell neuronopathy. Imaging markers have been developed to differentiate PML from new multiple sclerosis lesions and to facilitate the early identification of pre‐clinical manifestations of PML and its immune reconstitution inflammatory syndrome. PML can be diagnosed either by brain biopsy or by clinical, radiographic and virological criteria. Experimental treatment options including immunization and modulation of interleukin‐mediated immune response are emerging. PML should be considered in any patient with compromised systemic or central nervous system immune surveillance presenting with progressive neurological symptoms.